Case for Folk Valuation Of Plant Genetic Resources: Redeeming Nikolay Vavilov's Multiculturalist Plant Conservation Principles - Wall, Jeffrey (White Horse Press, 2025)
This work brings together evidence from the historical, ethical and cross-cultural  dimensions of Plant Genetic Resource (PGR) conservation to argue for an accounting of diverse folk value – i.e. value central to the cohesion and survival of particular peoples or  nations  –  in  the  collection  and  safeguarding  of  the  precise  plants  that  humankind needs to survive well. I argue that, without the original commitment to the simultaneous defence of biological and cultural survival that gave rise to PGR conservation in the men-acing Soviet Union, today’s stringently utilitarian valuation of PGR risks further eroding the  traditional  and  Indigenous  motivations  and  traditions  that  have  stewarded  PGR  into the present and that continue to power plant conservation around the world. By ac-counting for the breathtaking variation in folk value for plants within collections, PGR maintenance  and  conservation  can  construct  and  safeguard  more  desirable  and  more  important plant collections than those that currently exist, while bolstering the world’s persistent and diverse cultures of plant conservation. Such an approach is congruent with the deeper scientific truth for which Russian agronomist and botanist Nikolay Vavilov stood and for which he was martyred: that we shall not survive biologically without the cultural diversity that is the fountain head of humanity’s global plant endowment.